Efektivitas Salad Tauge (Phaseolus Aureus) Dalam Meningkatkan Kadar Hemoglobin Pada Remaja Putri Dengan Anemia Ringan Di SMK Unitomo Surabaya - Purwitasari, Alief Ayu; Kusumawardani, Lentera Afrida; Badrus, Arkha Rosyaria (Rena Cipta Mandiri, 2025)
Anemia is a prevalent nutritional problem among adolescent girls, impacting their health and academic performance. One effective and affordable alternative intervention is the use of local iron-rich foods, such as mung bean sprouts (Phaseolus aureus). This study aimed to examine the effectiveness of consuming mung bean sprout salad in increasing hemoglobin levels in adolescent girls with mild anemia. The study population consisted of 150 female students at SMK Unitomo Surabaya. A sample of 30 individuals was selected using purposive sampling. The research design was pre-experimental with a one-group pretest-posttest approach. Respondents received an intervention of 200 grams of mung bean sprout salad per day for 14 days. Hemoglobin levels were measured before and after the intervention using the cyanmethemoglobin method. The results of the paired sample T-test showed a significant increase in hemoglobin levels after the intervention (p < 0.05). These findings indicate that consuming mung bean sprout (Phaseolus aureus) salad is effective in increasing hemoglobin levels and can serve as an alternative intervention to reduce the prevalence of anemia in adolescent girls.